Marketing Mix Strategy to Increase Sales Volume of Wedding Packages at CV. Glow Wedding and Event Planner Bali - I Gede Mahesa Pradyana; Ratri Paramita; I Gusti Ngurah Agung Suprastayasa (PT FORMOSA CENDEKIA GLOBAL, 2025)
Bali is an area with very rapid tourism development as evidenced by foreign tourists who make Bali one of their destinations. This study aims to understand how the marketing mix strategy to increase the sales volume of wedding packages at CV. Glow Wedding and Event Planner Bali. The research method used is qualitative descriptive with data collection conducted through interviews, observations, and documentation studies. Qualitative descriptive data analysis techniques are analyzed using the SWOT matrix through the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence). Based on the results of this study, 4 marketing strategies were found, namely SO (Strength Opportunities) expanding relations and highlighting the flexible prices owned by the company, ST (Strength Threats) increasing the focus of wedding product promotions and making more attractive promotions, WO (Weaknesses Opportunities) adding a variety of wedding packages, WT (Weaknesses Threats) Maximizing promotions that have been carried out by conducting research on similar companies related to promotions, promotional media and prices.